2018
DOI: 10.4336/2018.pfb.38e201701522
|View full text |Cite
|
Sign up to set email alerts
|

Interceptação de Sinoxylon unidentatum (Coleoptera: Bostrichidae) no Rio de Janeiro, Brasil

Abstract: Resumo -A ocorrência da praga quarentenária (A2), Sinoxylon unidentatum Fabricius (Coleoptera: Bostrichidae) foi confirmada e interceptada no Porto do Rio de Janeiro, em paletes oriundos da Indonésia. Constatou-se que o brometo de metila não foi suficiente para inibir a ação dos insetos nos paletes. Sugere-se, como medida de monitoramento, a instalação de armadilhas etanólicas nos locais de armazenamento e trânsito de madeiras ou material lenhoso. Interception of Sinoxylon unidentatum (Coleoptera: Bostrichidae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Part of the Community of these groups are omnivores or simply insectivorous, thus contributing to the control of the population of beetles. However, Scolytinae and Bostrichidae representatives are in millimetric scale, which hinders its predatism by terrestrial tetrapoda, leaving the invertebrate parasitoids, predators and pathogens as environmental resistance (Xavier et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Part of the Community of these groups are omnivores or simply insectivorous, thus contributing to the control of the population of beetles. However, Scolytinae and Bostrichidae representatives are in millimetric scale, which hinders its predatism by terrestrial tetrapoda, leaving the invertebrate parasitoids, predators and pathogens as environmental resistance (Xavier et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the capture and monitoring of bostrichid species are often carried out in forest entomology studies (CARVALHO; TREVISAN, 2015). XAVIER et al (2018), by referring to the detection of quarantine bostrichid species S. unidentatum ;and BOONE et al (2019), by referring to Cerambycidae belonging to genus Monochamus, equally suggested that monitoring, based on entomological traps, was carried out in harbors and airports, mainly in locations where there is storage and transit of log and wooden materials. Therefore, this strategy, along with customs' inspection, can improve the efficiency and early detection of quarantine organisms, a fact that would allow sanitary measures to be taken in anticipation to rule out the insect in question and, consequently, to avoid its outspread in the environment.…”
mentioning
confidence: 99%